(untitled) (Literary Voice, 2024)
The present paper attempts to analyse the complex and ambiguous phenomenon of the very movement of postmodernism in Yann Martel’s distinguished novel Life of Pi. Owing to the techniques and strategies employed in this novel, it can be called the true representative of postmodern fiction. As it breaks with realism and avoids rigid genre distinction, postmodernism deconstructs the wholeness and completeness associated with conventional storytelling ways. There is use of postmodern narrative as the novel is highly self-reflexive and Martel also experiments with intertextuality and historiographic metafiction. He weaves this novel with extraordinary and unusual events. By blending facts and fiction, he makes space for the readers for different interpretations. The contours of postmodern techniques such as fragmentation, metafiction, multiple points of view, advocacy of plurality of histories, and sheer rejection of grand narratives are used in this novel. Out here Martel delineates the chaotic condition of the postmodern world through Life of Pi.